Banking in Sub-Saharan Africa : What Went Wrong? - Le Gall, Francoise (IMF Working Papers; Working Paper ;, 2004)
The purpose of this paper is to study the origins of banking crises in sub-Saharan Africa, drawing upon the experience of ten countries during the period 1985-95. It examines, in particular, which factors were the most important sources of these crises. The conclusions underscore that the banking crises examined did not represent an entirely special case-a number of factors identified in the general literature, including macroeconomic shocks, were highly relevant-but note that several of their features were nonetheless specific to this part of the world. These banking crises were the very prototype of endemic crises associated with heavy government intervention in the banking system. In this regard, the paper analyzes the complex role of the government in banking in sub-Saharan Africa, the many channels through which governments intervened, and the economic and institutional environment in which the banks operated.